2012
DOI: 10.1108/09513541211201979
|View full text |Cite
|
Sign up to set email alerts
|

Challenges in designing student teaching evaluations in a business program

Abstract: Purpose -This article aims to present an empirical analysis of the effects of changes in the student teaching evaluation (STE) form in a business school. Design/methodology/approach -The authors discuss a case of STE re-design in a business school that focused on improving the STE instrument. They utilize empirical data collected from students that completed both the original and the revised STE form in several semesters of undergraduate economics courses to examine the effect of changing the evaluation scale … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
20
0
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(23 citation statements)
references
References 24 publications
1
20
0
2
Order By: Relevance
“…Among various aspects of learning outcomes, instructional quality has been the central focus (Kwan, 1999). Perhaps, the most widely used assessment tools for measuring instructional quality in the higher education setting is student evaluations of teaching (SET) (Chulkov and Van Alstine, 2012; Steinberg and Kraft, 2017). While SET plays a pivotal role in faculty promotion, tenure and/or merit raise decisions (Dommeyer et al , 2004), SET also provides important feedback to the faculty regarding how the course may be adjusted and what teaching techniques may be adopted.…”
Section: Introductionmentioning
confidence: 99%
“…Among various aspects of learning outcomes, instructional quality has been the central focus (Kwan, 1999). Perhaps, the most widely used assessment tools for measuring instructional quality in the higher education setting is student evaluations of teaching (SET) (Chulkov and Van Alstine, 2012; Steinberg and Kraft, 2017). While SET plays a pivotal role in faculty promotion, tenure and/or merit raise decisions (Dommeyer et al , 2004), SET also provides important feedback to the faculty regarding how the course may be adjusted and what teaching techniques may be adopted.…”
Section: Introductionmentioning
confidence: 99%
“…If implemented correctly, student evaluations of teaching and learning can play an important role in the delivery of quality higher education. While feedback from students about their learning experiences is predominantly used by universities to inform promotion and tenure decisions (Kember, Leung, and Kwan 2002) and aid professional development (Chulkov and van Alstine 2012), it can also provide valuable insights into the strengths and weaknesses associated with the delivery of a particular course or programme (Ahmadi, Helms, and Raiszadeh 2001;Shah and Nair 2009;Blair and Valdez Noel 2014;Mohammed and Pandhiani 2017). Furthermore, the data gathered from course and lecturer evaluations could provide university administrators with important insights into what motivates students and how to respond appropriately to students' changing needs (Grebennikov and Shah 2012;Smithson et al 2015;Grebennikov and Shah 2017;Blair and Valdez Noel 2014).…”
Section: Introductionmentioning
confidence: 99%
“…It is used by administrators and instructors to make important decisions regarding development of the course and the instruction (Al-Issa & Sulieman, 2007;Ali & Ajmi, 2013;Beuth et al, 2015;Driscoll & Cadden, 2010). Also, it is used by students to make better decisions regarding which course they want to take and to be aware of the course levels of difficulty before the registration process (Adams & Umbach, 2012;Ali & Ajmi, 2013;Atek, Salim, Ab Halim, Jusoh, & Yusuf, 2015;Beuth et al, 2015;Brockx, Spooren, & Mortelmans, 2011;Chulkov & Jason Van, 2012;Donnon, Delver, & Beran, 2010;Driscoll & Cadden, 2010;Fah, Yin & Osman, 2011). Furthermore, SET is considered an important tool that could have negative impacts on the development of teaching if it does not give accurate results (Ali & Ajmi, 2013).…”
Section: Background Of the Problemmentioning
confidence: 99%
“…Researchers reported that educators face different challenges when it comes to designing SET. For example, shifting from a four-point scale to a five-point scale in SET affected the results of SET and led the students to give less positive feedback (Chulkov & Jason Van, 2012). Such a finding suggests that researchers who had used five-point scale might have found more negative rating scores than those who used a four-point scale.…”
Section: Challenges In Setmentioning
confidence: 99%
See 1 more Smart Citation